The Influence of Office Facilities, Work Discipline and Spatial Planning on the Performance of Administrative Employees at High Schools and Vocational Schools in Banggai Islands Regency - Hafit Bokko; Andi Mattulada; Nursiah (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
This study aims to find out and analyze office facilities, to find out that work discipline and office space layout partially affect the performance of administrative employees in high schools and vocational schools in Banggai Islands Regency and to find out and analyze office facilities, work discipline and office space simultaneously affect the performance of administrative employees in high schools and vocational schools in Banggai Islands Regency. Research sites in high school and vocational schools in Baggai Islands Regency. Validity and reliability test, the number of samples is 57 and the significance level is 5%, then the R table is 0.261 with the Cronbach Alpha method obtained a critical point of 0.6. So from all X1 obtained 0.808 > 0.6 (reliable), X2 obtained 0.801 > 0.6 (reliable) and X3 obtained 0.848 > 0.6 (reliable). And Y is obtained 0.870 > 0.6 (reliable) from each statement r calculation is greater than r table, so it is concluded that all data are valid. Variable X1 has a sig value of 0.001 and a calculated t-value of 3.422. Since the sig-value (0.001) is lower than 0.05 and the calculated t-value (3.422) is greater than the t-table (2.006), H01 is accepted, meaning that X1 exerts a significant influence on Y. Variable X2 has a sig value of 0.000 and a calculated t-value of 4.577. Since the value of its sig (0.000) is lower than 0.05 and the value of the calculated t (4.577) is greater than the t of the table (2.006), H02 is accepted, meaning that X2 exerts a significant influence on Y. Variable X3 has a sig value of 0.418 and a calculated t-value of -0.816. Since the sig value (0.418) is greater than 0.05 and the calculated t value (-0.816) is greater than the -t table (-2.006), H03 is rejected, meaning that X3 does not have a significant influence on Y.